The Effect of Cognitive Conflict Strategies on Students' Cognitive Learning Outcomes - Widia Widia; Suhirman Suhirman; Muhammad Suhardi; Saiful Prayogi; Muhammad Yamin; Muhammad Salahuddin; Lutfin Haryanto; Ewisahrani Ewisahrani; Ilyas Ilyas; Mujitahid Mujitahid; E Nursa’ban E Nursa’ban (Postgraduate, University of Mataram, 2022)
An important aspect of learning outcomes at all levels of education is cognitive learning outcomes, and to achieve optimal cognitive learning outcomes, multi-method intervention is needed. This study aims to determine the effect of using cognitive conflict strategies on students' cognitive learning outcomes. Experimental research with one group pretest-posttest design was conducted in this study. A total of thirty-five students as the research sample, sample came from one of the high schools in West Lombok, West Nusa Tenggara. Cognitive conflict strategies are conducted in the material of continuous straight motion and uniformly changing straight motion. Measurement of cognitive learning outcomes using a test instrument (essay test) as many as six test items that accommodate cognitive level 1 (C1) to 6 (C6) and these are given to students as pretest and posttest. Descriptively, the results showed that cognitive learning outcomes increased after learning using cognitive conflict strategies (mean: 3. 4803) significantly (p: 0.000) with an n-gain of 0.74 in the high category. These results imply that cognitive conflict strategies are effective for improving students' cognitive learning outcomes